Capacidad de carga turística en la zona de uso público de la isla San Gregorio perteneciente al archipiélago de Jambelí - Suarez Barba, Ginna Cecibel (My University, 2021)
In recent years, San Gregorio Island has become a potential and representative tourist attraction of the province of El Oro. The incredible beachfront that it has in addition to promoting the destination has generated an increase in the interest of people to visit it and carry out sun and beach activities. This massive influx of tourists can bring collapse and the generation of impacts, if it does not have the tools that allow proper management and planning of the place. The present investigation was structured under the combination of qualitative-quantitative methods, which will know the reality of the object of study through bibliographic sources, along with the numerical calculation on the phenomenon studied, in addition to being of a bibliographic, field and descriptive type. The main objective was to determine the tourist load capacity in the area of public use of the Island in order to propose alternatives that allow the sustainable management of the area; under the methodology proposed by Cifuentes, which mentions the calculation of three levels of load capacity (physical, real and effective. The results obtained for the first level were 3,493 users day considering the entire available area, however, subject to correction factors such as precipitation, erodability and solar brightness, the real capacity was 1,173 tourists day, finally, considering the handling that the beach has the average low to 624 users day. Reason why it is necessary to implement strategies to promote sustainable tourism.
En los últimos años la Isla San Gregorio se ha convertido en un atractivo turístico potencial y representativo de la provincia de El Oro. El increíble frente playero que posee en suma a la promoción del destino ha generado aumento en el interés de las personas por visitarlo y realizar actividades de sol y playa. Esta masiva afluencia de turistas puede traer consigo el colapso y la generación de impactos, si no cuenta con las herramientas que permitan un adecuado manejo y planificación del lugar. La presente investigación se estructuró bajo la combinación de los métodos cualitativo-cuantitativo; el cual permitió conocer la realidad del objeto de estudio mediante fuentes bibliográficas, a la par del cálculo numérico sobre el fenómeno estudiado, además es de tipo bibliográfico, de campo y descriptiva. El objetivo principal fue determinar la capacidad de carga turística en la zona de uso público de la Isla con el fin de proponer alternativas que permitan el manejo sostenible del área; bajo la metodología propuesta por Cifuentes, el cual menciona el cálculo de tres niveles de capacidad de carga física, real y efectiva. Los resultados obtenidos para el primer nivel fueron de 3.493 usuarios día considerando toda el área disponible, sin embargo, sometido a factores de corrección como precipitación, erodabilidad y brillo solar la capacidad real fue de 1.173 turistas día, por último, considerando el manejo que tuvo la playa el promedio bajo a 624 usuarios día. Motivo por el cual fue necesario la implementación de estrategias que permitan promover un turismo sostenible.
Keywords: TURISMO SOSTENIBLE; CARGA TURISTICA; ESTRATEGIA SOSTENIBLE